An English School Approach to Public Diplomacy – social power and norm creation. - de Lima Junior, Antonio Ferreira (Conjuntura internacional, 2015)
This article attempts to lift the veil on the connection between public diplomacy practices and some tenets of the English School. The general argument is that in the context of an anarchical society of states that govern themselves through shared institutions, norms and values, public diplomacy is an important means to influence the manufacturing of the norms and values that functions as the milieu of world politics. It is also maintained that states with effective public diplomacy policies are those with the greatest social power.